Minimal projections and largest simplices - M. V. Nevskij (Моделирование и анализ информационных систем)
It is proved that the minimal norm On of a projection in linear interpolation on the n-dimensional cube On = [0,1]n satisfies the condition On = 0(n1/2), n G N. With the previous results of the author it means that On ~ n1/2. The upper estimates are provided by the projection with knots of interpolation in vertices of а largest simplex in On.